Propuesta para la creación de tres helados no convencionales a base de papa (Solanum tuberosum), arazá (Eugenia stipitata) y zapallo (Cucurbita maxima) aplicando técnicas vanguardistas - Carlosama Cabascango, Maritza Alexandra (2023)
Ice cream is not simply a cold summer dessert, products such as potato (Solanum tuberosum), arazá (Eugenia stipitata) and pumpkin (Cucurbita maxima) have a high content of antioxidants and amino acids as well as vitamins, which when fused with vanguard techniques allow obtaining novel unconventional ice creams with high nutritional value. This research proposes to apply vanguard techniques in the elaboration of non-conventional ice creams to encourage the consumption of potato, arazá and pumpkin. The methodology is based on an applied research with a mixed approach, it is aligned with the inductive deductive and analytical-synthetic research methods, in the same way three research techniques are applied: survey, interview and observation\; the calculation of the sample was made with the EAP of the city of Ibarra with 63,984 people, by applying the formula 383 surveys were obtained as a result. The most relevant results allowed obtaining a list of sweet recipes with potato, arazá and pumpkin\; the three fruits have amino acids, antioxidants, vitamins and minerals that provide high nutritional value\; the use of liquid nitrogen was considered expensive, not very useful for the manufacture of ice cream for distribution and at the same time old-fashioned\; for the preparation of ice cream is recommended the use of sugars derived from corn for its antifreeze power\; the application of glucose, sucrose and honey should be regularized to obtain the texture and sweetness required. Finally, it was concluded that the “ratona morada” potato was the most suitable, since it contributed flavor, texture and characteristic color\; the use of arazá for the preparation of a sorbet should be combined with another fruit because of its extreme acid flavor\; and pumpkin is a product that can be worked with or without the presence of a dairy product due to its good texture.